Low risk for microbial contamination of syringe and tube feeding bag surfaces after multiple reuses with home blenderized tube feeding. (2nd March 2022) - Milton, Debra; Murphy, Brie; Johnson, Teresa W.; Carter, Holly; Spurlock, Amy Y.; Hussey, Jenna; Johnson, Kelly
Abstract: Background: Guidelines for the reuse of enteral tube feeding (ETF) equipment guidelines are limited to manufacturer recommendations. ETF equipment reuse studies are needed as the enteral population has increased, along with blenderized tube feeding (BTF). Methods: This experiment tested microbial contamination of a reusable gravity feeding bag and syringe after 15 BTF reuses and cleanings. Eight bags and syringes were filled with the BTF, held at room temperature for 20 min, and then emptied, washed, and air dried. After the last air drying, the inner surfaces of the bag and syringe were swabbed, and aerobic microbial counts were performed using serial dilutions and plate counts. Results: The microbial counts for all syringes and six bags were <1 colony‐forming unit (CFU)/cm 2 ; one bag was <5 CFU/cm 2 and one bag was 12.5 CFU/cm 2 . No legal guidelines for surface cleanliness exist for the food sector. Several studies propose a safe microbial level to be <2.5 CFU/cm 2, and the European Commission recommended <10 CFU/cm 2 . Based on these proposed guidelines, microbial counts of all syringes and seven bags were within the proposed guidelines, except for one bag just above 10 CFU/cm 2 . Conclusion: The feeding bag used in this study may be used multiple times for BTF with a reduced risk of microbial contamination when manufacturer's cleaning guidelines are followed. Although bolus tube feeding is an off‐label use for syringes, they are frequently used for BTF, and in this study the cleaning after 15 uses over 5 days was effective to reduce microbial counts.